Gestión presupuestaria y la inversión en sectores vulnerables del GAD parroquial de San Juan del cantón Riobamba, periodo 2023-2024 - Gualpa Orozco, Candy Maritza (2025)
Budget management is an element of great relevance for public administration since it establishes how financial resources are allocated and distributed for the benefit of the population. Therefore, the purpose of this study is to analyze budget management to determine the efficiency and effectiveness of investment in vulnerable sectors of the Decentralized Autonomous Government of San Juan, Riobamba canton, period 2023-2024. For its preparation, a descriptive and exploratory methodology was applied, with a qualitative and quantitative approach with an inductive and analytical method, where the techniques used were the survey and the interview. The sample taken for the application of the instruments were 5 community leaders who gave their point of view on the problem raised. The results obtained indicated that there is a notable reduction in the budget allocated to vulnerable groups during the period 2024, which puts their sustainable development at risk. In this sense, it was concluded that inadequate budget management negatively influences the most vulnerable sectors since there is a perception that the Parish GAD does not invest adequately in these sectors.